2012
DOI: 10.1007/s12603-011-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an 8-weeks aerobic training program in elderly on oxidative stress and Hsp72 expression in leukocytes during antioxidant supplementation

Abstract: This study provides evidence that in elderly, increased concentration of antioxidant vitamins C and E is associated with a reduction in oxidative stress and leukocytes Hsp72. In this context, 8 weeks of aerobic training has no impact on oxidative stress or leukocytes Hsp72 expression in elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
1
11
1
6
Order By: Relevance
“…On the other hand, it has been also demonstrated that the expression of HSP70 in leukocytes is increased after a half marathon (Fehrenbach et al 2000). However, 1-h walking sessions, 3 days a week on a running track for 8 weeks, had no impact on leukocyte Hsp72 expression in elderly people (Simar et al 2012). Our exercise protocol seems to be intense enough to promote an increase of Hsp70 in PBMC, which could be the origin of the circulating Hsps.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been also demonstrated that the expression of HSP70 in leukocytes is increased after a half marathon (Fehrenbach et al 2000). However, 1-h walking sessions, 3 days a week on a running track for 8 weeks, had no impact on leukocyte Hsp72 expression in elderly people (Simar et al 2012). Our exercise protocol seems to be intense enough to promote an increase of Hsp70 in PBMC, which could be the origin of the circulating Hsps.…”
Section: Discussionmentioning
confidence: 99%
“…In the same experiment, cycling at 70% of VO 2peak for 45 min increased muscle HSP72 levels significantly and tended to increase HSP60 levels in controls groups, whereas no exercise-induced HSP response was seen in the vitamin C-supplemented group [76]. Antioxidant supplementation decreased resting and post-exercise oxidative stress markers similarly in both groups, and lowered oxidative stress was parallel with decreased expression of HSP72 levels in monocytes and granulocytes in both groups [95]. In a more recent study, interaction of antioxidant supplementation with aerobic training on systemic oxidative stress and HSP72 expression was investigated in the elderly at mean age of 74.6 yr. All subjects were supplemented with vitamin C (500 mg/day) and vitamin E (100 mg/day) for 8 weeks and randomly divided either to sedentary or training group [95].…”
Section: Stress Proteins and Dietary Supplementsmentioning
confidence: 86%
“…In another antioxidant supplementation study in healthy, untrained males, oral supplementation of vitamin C 0.5 g/day for 8 weeks increased baseline HSP70 content in vastus lateralis muscle [76]. In a more recent study, interaction of antioxidant supplementation with aerobic training on systemic oxidative stress and HSP72 expression was investigated in the elderly at mean age of 74.6 yr. All subjects were supplemented with vitamin C (500 mg/day) and vitamin E (100 mg/day) for 8 weeks and randomly divided either to sedentary or training group [95]. The authors concluded that, although vitamin C-supplementation up-regulated baseline expression of HSPs, it also attenuated exercise-induced HSP and antioxidant defenses.…”
Section: Stress Proteins and Dietary Supplementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascorbic acid is a known reducing agent for oxidized vitamin E, and it can then limit its accumulation in its 2. 41,[55][56][57][58] In independently living, healthy elderly people, combining vitamin C and E, using either a high (1000 mg) or moderate (500 mg) dose of ascorbic acid with 400 IU of α-tocopherol daily for 6 months, leads to an increase in systemic levels of both vitamins, with no difference between the two doses of ascorbic acid. 37 This observation has led to the hypothesis that supplementations combining multiple antioxidants could provide greater benefits than isolated vitamins or trace elements.…”
Section: Combination Of Multiple Vitamins and Trace Elementsmentioning
confidence: 99%